T-X phase diagram of (NH4)2SO4/H 2O - Yurtseven, Hasan Hamit; Enginer, Y.; Şen, Sema; Saliho?lu, Selami (Indian Chemical Society, 2007)
Using the mean field theory, we obtain the phase line equations for the liquid-solid I, liquid-solid II and solid I-solid II transitions in (NH 4)2SO4/H2O. We fit our phase line equations to the experimental T-X phase diagram of this system. Thus, we are able to obtain the temperature and concentration dependencies of the order parameters and the free energies in this system. © 2021 Elsevier B.V., All rights reserved.
Keywords: Ammonium sulfate; Mean field theory; Phase diagram